Analisis Dampak Volatilitas Pasar, Faktor Fundamental, dan Sentimen Investor terhadap Keputusan Investasi Saham pada Mahasiswa Program Studi Manajemen Fakultas Ekonomi Universitas Slamet Riyadi Surakarta Tahun 2024 - Charlie Kuncara Jati; Dorothea Ririn Indriastuti (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2024)
Abstract. This study aims to analyze the effect of Market Volatility, Fundamental Factors, and Investor Sentiment on Stock Investment Decisions of Management Study Program Students, Faculty of Economics, Slamet Riyadi University, Surakarta. The research sample was taken using the Slovin technique, which resulted in a sample size of 78 students. The data collection technique was carried out through a questionnaire distributed to students who met the criteria. The research instrument test used validity and reliability tests. The classical assumption test used multicollinearity test, autocorrelation test, heteroscedasticity test, and normality test. The data analysis technique used descriptive analysis, multiple linear regression analysis, t-test, F-test and coefficient of determination (R²). The conclusion obtained from this study is that Market Volatility, Fundamental Factors, and Investor Sentiment have a significant influence on students' Stock Investment Decisions. These findings indicate that a deep understanding of the capital market and the factors that influence it is very important in making the right investment decisions. The results show that the coefficient of determination (adjusted r2) for this model is 0.700, meaning that the contribution of the independent influence of market volatility, fundamental factors and investor sentiment to stock investment decisions is 70%. The rest (100% - 70%) = 30% is explained by other variables outside the model such as gender, age, overconfidence, market awareness, income, etc.